Pengabdian Kepada Masyarakat Melalui Kuliah Kerja Nyata (KKN) di Desa Langkapsari Kecamatan Banjaranyar - Fachmi Syam Arifin; Gilang Brilian; Rifal Amalindi; Aulia Fitrahunisa; Tarisa Agustria (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Community Service Program (CSP) are part of the Tridharma of higher education, which requires students to play an active role in empowering society through education, research and service. This article discusses the implementation of the Galuh Ciamis University CSP, which took place in Langkapsari Village, Banjaranyar District, Ciamis Regency, with a focus on the main aspects: Increasing community capacity through optimizing Natural Resources and Strengthening Local Culture. The programs carried out include planting 100 tree seedlings, socializing verticulture planting, cultural performances, and creating a village website. Through a participatory educational approach and observations during CSP, this activity aims to improve the quality of community awareness of the environment. The results show active community participation in the program. This article also identifies the challenges faced and provides recommendations for developing CSP programs in the future.